1994
DOI: 10.1029/93ja03583
|View full text |Cite
|
Sign up to set email alerts
|

The proton cyclotron instability and the anisotropy/β inverse correlation

Abstract: Spacecraft observations in the strongly compressed subsolar magnetosheath show an inverse correlation between the proton temperature anisotropy (Wlp/•l p • 1 where _L and II denote directions perpendicular and parallel to the background magnetic field) and the parallel proton/• (/•llp)' This manuscript uses one-dimensional hybrid simulations of the proton cyclotron anisotropy instability in homogeneous electron-proton plasmas to study this correlation which may represent a limited closure relation for fluid th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
142
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 38 publications
10
142
2
Order By: Relevance
“…This scattering thereby results in a more-thermalized equilibrium state Denton et al, 1994b;Gary and Lee, 1994;Gary et al, 1993a;Gary et al, 1994a;Gary et al, 1994b;Gary et al, 1994c). Moreover, this work established a significant correlation between the proton temperature anisotropy and the proton in the magnetosheath, and one which has the same slope as that required to keep the Alfve´n/ion-cyclotron mode near to marginal stability.…”
Section: Alfve´n/ion-cyclotron Wavessupporting
confidence: 51%
See 1 more Smart Citation
“…This scattering thereby results in a more-thermalized equilibrium state Denton et al, 1994b;Gary and Lee, 1994;Gary et al, 1993a;Gary et al, 1994a;Gary et al, 1994b;Gary et al, 1994c). Moreover, this work established a significant correlation between the proton temperature anisotropy and the proton in the magnetosheath, and one which has the same slope as that required to keep the Alfve´n/ion-cyclotron mode near to marginal stability.…”
Section: Alfve´n/ion-cyclotron Wavessupporting
confidence: 51%
“…This paradigm suggests that these waves are being driven within the magnetosheath and in turn react back on the particle distributions to reduce the mode growth rate from large values to that corresponding to further macroscopic pumping rates. Artificially driven simulations (Gary et al, 1994c;Denton et al, 1993) have been used to support this paradigm, although they do not completely represent the pumping processes in the magnetosheath. The Alfve´n/ ion-cyclotron mode should be particularly effective at low .…”
Section: Alfve´n/ion-cyclotron Wavesmentioning
confidence: 99%
“…at frequencies below f ci . For the magnetosheath conditions (T ⊥ >T ) the linear Vlasov theory for homogeneous plasmas predicts that if the ion plasma beta β=8πp/B 2 0 , the ratio between the pressure of the ions p and the magnetic pressure, is small (β≤1) Alfvén Ion Cyclotron (AIC) waves will grow with wave vectors mainly parallel to the background field k k ⊥ , while for a high beta (β≥5) mirror waves with k ⊥ k will grow (Schwartz et al, 1996;Gary et al, 1994b). These waves then scatter and diffuse the particles, reducing the anisotropy.…”
Section: The Earth Magnetosheathmentioning
confidence: 99%
“…Our previous research with single proton bi-Maxwellian distributions [Gary et al, 1994[Gary et al, , 1995[Gary et al, , 1997] has shown that there exist constraints on both the proton anisotropy and the saturation value of the fluctuating magnetic field energy density which may be expressed as con- Further study is necessary to more completely characterize (10).…”
Section: Simulation Ensembles: Mostly Magnetosonicmentioning
confidence: 99%